Acenocoumarol sensitivity and pharmacokinetic characterization of CYP2C9 *5/*8,*8/*11,*9/*11 and VKDRC1*2 in black African healthy Beninese subjects - ALLABI, CONSTANT AUREL; Horsmans, YVES; Alvarez', JEAN CLAUDE; BIGOT, KOFFI ANDRÉ (My University, 2012)
Abstract This study aimed at investigating the contribution of CYP2C9 and VKORCI genetie polymorphisms to inter-individual variability of acenocoumarol pharmacokinetics and pharmacodynamies in Black Africans from Benin. Fifty-onc hcalthy volunteers were genotyped for VKORC1 1173C>T polymorphism. Ali of the subjects had previously been genotyped for CYP2C9*5, CYP2C9*6, CYP2C9*8, CYP2C9*9 and CYP2C9*11 allcles. Thirty-six subjects were phenotyped with a single 8 mg oral dose of acenocoumarol by measuring plasma concentrations of (R)- and (S)-acenocoumarol 8 and 24 h after the administration using chiral liquid-chromatography tandem massspectrometry. International normalized ratio (INR) values were determined prior to and 24 h after the drug intake. The allele frequency of VKORCI variant (l173C>T) was 1.96% (9S% CI 0.0-4.6S%). The INR values did not show statistically significant difference between the CYP2C9 genotypes, but were correlated with body mass index and age at 24 h post-dosing (P < O.OS). At 8 h post dose, the (S)-acenocoumarol concentrations in the CYP2C9*5/*8 and CYP2C9*9/*11 genotypes were about 1.9 and S.l fold higher compared with the CYP2C9*1/*1 genotype and 2.2and 6.0-fold higher compared with the CYP2C9*1/*9 group, respectively. The results indicated that pharmacodynamie response to acenocoumarol is highly variable between the subjects. This variability seems to be associated with CYP2C9*5/*8 and *9/*11 variant and demographie factors (age and weight) in Beninese subjects. Signifieant association between plasma (S)-aeenocoumarol concentration and CYP2C9 genotypes suggested the use of (S)-acenocoumarol for the phenotyping purpose. Larger number of subjects is needed to study the effect of VKORCI l173C>T variant due to its low frequency in Beninese population.
Keywords: CYP2C9· VKORCI . Aeenoeoumarol .; INR . Benin . African